The Impact of Project-Based Learning with Delphi Software on Students' Computational Thinking Skills - Suci Juniarto; S Sutama; Anam Sutopo; Harun Joko Prayitno; Endang Fauziati; Ahmad Muhibbin; S Suansah (Proceeding International Conference on Mathematics and Learning Research, 2025)
Problem-solving skills and Computational Thinking (CT) are very important skills in today's digital era. Improving the ability of CT mathematics education students is becoming increasingly important as the need for skills develops in the 21st century. Project-based learning (PBL) has been shown to be effective in improving these skills. However, the limited research examining the impact of PBL with Delphi software on computational thinking skills in mathematics education encourages the need for further research. This study aims to explore the impact of project-based learning with Delphi on improving students' computational thinking skills. This type of research is a quantitative research with a quasi-experimental design. The population is 6th semester students of mathematics education. The sample consisted of two classes totaling 40 students. The results of the T test showed that the experimental group showed a significant improvement compared to the control group (t = 4,102, p < 0.05). The implications of this research are important for the development of a technology-based mathematics education curriculum. It is recommended for further research with a larger sample of different institutions to explore the long-term impact as well as other factors that may affect project-based learning outcomes.